Evaluating the Protective Behavioral Strategies for Marijuana Scale (PBSM) short-form: Support for a two-factor structure and measurement invariance. (1st July 2022) - Jordan, Hallie R.; Hoover, Skyler M.; Prince, Mark A.; Madson, Michael B.; ,; Ham, Lindsay S.; Hurlocker (Co-PI), Margo C; Leffingwell, Thad; Looby, Alison; Lui, P. Priscilla; Madson (Co-PI), Michael B; Meier, Ellen; et al.
Abstract: Background: The present study evaluated the two-factor structure of the Protective Behavioral Strategies for Marijuana Scale (PBSM-SF) Short-Form, a 13-item measure of harm reduction behaviors related to cannabis use. Additionally, the PBSM was evaluated for measurement invariance based on sex and state cannabis legalization status. Method: Participants were 1, 048 college students ( M age = 19.00) reporting past 30-day cannabis use who primarily identified as White (75.5%) females (64.9%) recruited from 11 universities in 11 states representative of the United States. All participants provided demographic information and completed the PBSM-SF, Marijuana Use Grid assessing cannabis use frequency, Cannabis Use Disorder Identification Test-Revised assessing hazardous cannabis use, and Brief Marijuana Consequences Questionnaire evaluating negative consequences. Results: The two-factor structure (i.e., Quantity and Context) of the PBSM-SF identified in Mian et al. (2021) was supported in the present study. Additionally, analyses demonstrated evidence of convergent and concurrent validity. Finally, the two-factor PBSM-SF demonstrated some degree of invariance by sex and state legalization status. Conclusions: This study provides additional support for a two-factor model of PBSM-SF (i.e., Quantity and Context) that functions similarly for men and women college students as well as for students from states without legalized cannabis use and states with legalized cannabis use. Highlights: This study provides confirms two subscales for the Protective Behavioral Strategies for Marijuana. The PBSM demonstrates evidence of convergent and concurrent validity with measures of marijuana use. The PBSM appears invariant for men and women as well as for students from states with and without legalized cannabis use.